Inovasi Teknologi Pembuatan Pakan Udang dengan Penambahan Tepung Kopasanda (Chromolaena odorata L.) di Desa Tamangapa Kecamatan Ma’rang Kab. Pangkep - Harlina, Harlina; Hadijah, Hadijah; Kamaruddin, Kamaruddin; Ernaningsih, Ernaningsih (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Tamangapa village, Ma?rang district is part of the community development program conducted by Universitas Muslim Indonesia in Pangkajene Kepulauan regency. The local shrimp farmers of Tamangapa village have been facing major issue due to expensive artificial feed and high mortality rate. In order to solve the needs of feed and high mortality rate for farmed fish or shrimp, the source of the natural ingredients using kopasanda leaves Chromolaena odorata L is required. The use of a natural ingredient is also used to prevent the vibriosis using simple technology such as the utilization of local raw materials which is affordable and locally available. The present community service aimed to provide the proper knowledge and skills to members of the fish/shrimp farmer?s group through counseling, training and mentoring. This community service program encouraged the local farmers to be able to utilize the local raw materials as a source of shrimp feed, use the feed pellet machine, and packaging leading to independent feed production. The participatory training method, lectures, forum group discussions, and practices of making shrimp feed and packaging were applied. The Implementation of the Community Partnership Program of Shrimp and Fish Cultivation Groups is independently able to produce organic fish or shrimp feed for farmer?s group leading to higher productivity of aquaculture.